2019
DOI: 10.3390/w11040694
|View full text |Cite
|
Sign up to set email alerts
|

Water-Worked Gravel Bed: State-of-the-Art Review

Abstract: In a natural gravel-bed stream, the bed that has an organized roughness structure created by the streamflow is called the water-worked gravel bed (WGB). Such a bed is entirely different from that created in a laboratory by depositing and spreading gravels in the experimental flume, called the screeded gravel bed (SGB). In this paper, a review on the state-of-the-art research on WGBs is presented, highlighting the role of water-work in determining the bed topographical structures and the turbulence characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Image reproduced from Padhi et al. (2019). (b) Schematic of flow structure in water column and porewater.…”
Section: Introductionmentioning
confidence: 99%
“…Image reproduced from Padhi et al. (2019). (b) Schematic of flow structure in water column and porewater.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bedload transport in rivers can be extrapolated using empirical models such as the one used by Radecki-Pawlik et al [2] for the Mlynne and Lososina Streams (Polish Carpathians). An extensive review on water-worked gravel bed natural evolution can be found in [3].…”
Section: Introductionmentioning
confidence: 99%
“…It includes nine papers, which can be classified into four categories. The first category is comprised of two review papers from Mrokowska and Rowiński [16] on bedload transport by unsteady flow and Padhi et al [17] on water-worked gravel beds. These papers deliver an excellent background that is useful for understanding and modeling bedload transport under unsteady flow conditions and for the morphological and flow characteristics in water-worked beds.…”
mentioning
confidence: 99%